Geographical information systems and spatial optimization - Faiz, Sami (CRC Press, 2013)
"Preface Geographical Information Systems (GIS) are becoming extremely important in various decision making processes. They provide an opportunity to make educated and profitable decisions. The trend is growing considerably, and GIS data is being used in complex decision-making. As such, it is essential to not only explore spatial data, but to also generate the best solution. The integration of GIS and optimization system is desirable for tackling such problems. This integration can be applied to numerous fields, such as hydrology and water resources, environment and ecology, waste management and urban planning, and routing problems. This book deals with the basic concepts of GIS and optimization. It provides an overview of various integration protocols that are termed as GIS-O integration strategies applied to practical applications. An integration approach for the vehicle routing problem with resource and distance requirements is developed and approved by numerical results. This book will be useful for researchers, decision makers, and practitioners who try to implement upgraded systems that derive benefits of both the GIS and the optimization"-- Provided by publisher.
"A Science Publishers book."
Keywords: Geographic information systems.; Geospatial data.; elektronické knihy; electronic books